PERFORMANS PRODUKSI DAN TEBAL KERABANG BURUNG PUYUH BETINA(Coturnix coturnix japonica) UMUR 6-14 MINGGU PADA LAMA PENCAHAYAAN YANG BERBEDA - Suleman, A.; Lambey, L.; Nangoy, F.; Laihat, J. (ZOOTEC, 2018)
PERFORMANCE PRODUCTION AND EGG SHELL THICKNESS OF QUAIL (Coturnix coturnix japonica) AT 6-14 WEEKS OLD AT DIFFERENT LIGHTING LENGTH. This study was done to determine the effect of the lighting length on the performance of quail production at 6-14 weeks old. This research was conducted at the experimental laboratory of Animal Production Department, Faculty of Animal Husbandry Sam Ratulangi University Manado, during the period from January 7, 2017 to March 3, 2017. The ration used was SP-22 commercial feed by PT. Sinta Fredmill. The total of quails used were 80 birds. Birds were maintained in a 60cm x 40cm baterrey system, using 5 watts power light. The variables measured were feed consumption, egg production and peak production, egg weight, and thickness of the egg shell. The design used in this study was a completely randomized design with 4 treatments and 5 replications. Each replication of experiment involved 4 quails with the treatments; R0 = 12 hours of illumination; R1 = 16 hours of illumination; R2 = 20 hours of illumination; R3 = 24 hours of illumination. Feeding and drinking water were prepared ad libitum. The result of the analysis showed that duration of lighting did not affect the averages of feed consumption, egg production, egg weight and egg shell thickness, but peak production could be reached more than 80% at the thirteenth week. Therefore, it can be concluded that the addition of light for female quail production at 6-14 weeks old did not affect feed consumption, peak production, egg weight, and thickness of the egg shellÂ Keywords: Quail, performance production, lighting length illumination